Follow-up on fertilizer distribution to rice farming groups using the k-means algorithm classification approach : ENGLISH - Mochamad Habil Noor; Fachrul Kurniawan; Muhammad Ainul Yakin (Institute of Computer Science (IOCS), 2024)
The distribution of fertilizers regulated in the Definitive Plan for Farmer Group Needs (RDKK) can be obtained by farmers through retail, which is specifically aimed at direct distributors, and the policies are regulated by the local regional government. The aim of this research is to develop a recommendation system that can assist the Pasuruan City Agriculture Service in making decisions regarding fertilizer distribution. In this research, an analysis and application of the K-Means classification method were carried out as a recommendation system for follow-up distribution of subsidized fertilizer. The K-Means method is used to group farmer groups based on several criteria, such as land area, amount of fertilizer received, and harvest yields. In this way, it is hoped that this method can provide more accurate recommendations for distributing subsidized fertilizer to rice farmer groups that need it. The research results show that the recommendation system developed can provide precise and accurate recommendations regarding the distribution of fertilizer to farmer groups. It is hoped that this system can help farmers increase their productivity and welfare